Simulation and Analysis of a Novel Isopropanol and Acetone Production via Propylene - Marco Vaccari; Federico Baglioni; Leonardo Zando; Leonardo Tognotti (Chemical Engineering Transactions)
Isopropanol (IPA) is an essential industrial solvent with growing demand, necessitating sustainable and cost-effective production methods. This study evaluates a novel integrated process for producing IPA and acetone via propylene hydration. Using UniSim Design©, advanced process simulation and heat integration techniques optimize energy efficiency and internal heat recovery, aligning with sustainability and regulatory goals. Sensitivity analysis reveals the economic feasibility is sensitive to fluctuations in feedstock and product prices, utility costs, and inflation rates, potentially impacting different performance indicators. The process also demonstrates flexibility in modulating IPA and acetone production to adapt to market changes. These findings provide insights into sustainable chemical production while addressing economic and regulatory challenges.